Friday

April 29, 2016
Total # Posts: 2,098

**math**

( - 6 ) + ( - 3 ) - ( - 1 ) - ( + 4 ) = - 6 - 3 + 1 - 4 = - 12
*January 7, 2013*

**Algebra**

a x + a y = a ( x + y ) a ( x + y ) = a ( x + y ) Identity
*January 6, 2013*

**math**

1 ft = 12 in 2 ft = 24 in 6 ft = 72 in 16 ft = 192 in 3 ft + 4 in + 2 ft + 10 in + 6 ft 8 in = 36 + 4 + 24 + 10 + 72 + 8 = 154 in 16 ft - 154 in = 192 in - 154 in = 38 in = 36 in + 2 in = 3 ft 2 in
*January 6, 2013*

**math**

( 3 / 5 ) / 4 = 3 / ( 5 * 4 ) = 3 / 20 m
*January 6, 2013*

**Math**

a = first number b = second number a - b = 3 Add b to both sides a - b + b = 3 + b a = b + 3 a ^ 2 + b ^ 2 = 89 ( b + 3 ) ^ 2 + b ^ 2 = 89 b ^ 2 + 2 * b * 3 + 3 ^ 2 + b ^ 2 = 89 b ^ 2 + 6 b + 9 + b ^ 2 = 89 2 b ^ 2 + 6 b + 9 = 89 Divide both sides by 2 b ^ 2 + 3 b + 9 / 2 = 89...
*January 4, 2013*

**Math**

W = Garden width H = Garden height A = Garden area L = W + 4 A = L * W 60 = ( W + 4 ) * W 60 = W ^ 2 + 4 W Add 4 to both sides 64 = W ^ 2 + 4 W + 4 ________________________________________ Remark : W ^ 2 + 4 W + 4 = ( W + 2 ) ^ 2 ________________________________________ 64...
*January 4, 2013*

**Math**

a = length of one side of the square W = Rectangle width H = Rectangle height A = Rectangle area W = a + 2 H = a - 2 A = W * H A = ( a + 2 ) * ( a - 2 ) = 32 32 = a ^ 2 + 2 a - 2 a - 4 32 = a ^ - 4 Add 4 to both sides 32 + 4 = a ^ - 4 + 4 36 = a ^ 2 a = sqrt ( 36 ) = 6 The ...
*January 4, 2013*

**math**

- 8 - 7 x > 6 Add 8 to both sides - 8 - 7 x + 8 > 6 + 8 - 7 x > 14 Divide both sides by - 7 ________________________________________ Remark: When you multiply or divide inequality by a negative number you must change the direction of the inequality. ...
*January 4, 2013*

**math question**

9.327 + 5.72 + 4.132 = 19.179 = 19.2 rounded to one decimal place
*January 4, 2013*

**math**

9 / 18 = 1 / 2 3 9 / 18 = 3 1 / 2 3 * 18 = 54 1 / 3 = 18 / 54 1 / 2 = 27 / 54 5 1 / 3 + ( - 3 9 / 18 ) = 5 1 / 3 - 3 9 / 18 = 5 1 / 3 - 3 1 / 2 5 + 18 / 54 - ( 3 + 27 / 54 ) = 5 - 3 + 18 / 54 - 27 / 54 = 2 - 9 / 54 = 2 - 9 / ( 9 * 6 ) = 2 - 1 / 6 = 1 + 1 - 1 / 6 = 1 + 6 / 6 - ...
*January 4, 2013*

**8thMath**

C = numbers of students in class Boys = 3 / 5 of the class ( 3 / 5 ) C = 24 Multiply both sides by 5 3 C = 24 * 5 3 C = 120 Divide both sides by 3 C = 120 / 3 = 40 girls = ( 2 / 5 ) * 40 = 80 / 5 = 16
*January 4, 2013*

**math**

limit ( 5000 t ^ 2) / ( t + 2 ) ^ 2 as t - > infinity = 5000 limit t ^ 2 / ( t + 2 ) ^ 2 as t - > infinity ________________________________________ t ^ 2 / ( t + 2 ) ^ 2 when t = infinity = infinity / infinity so you must use L'Hospital's rule ...
*December 29, 2012*

**HELPP math**

Go on : wolframalpha dot com When page be open in rectangle type : variance {13,14,29,26,41,53,60,7,89,14} and click option = Then in rectangle type : standard deviation {13,14,29,26,41,53,60,7,89,14} The variance = 685.156 approx. 685.2 The standard deviation = 26.1755 approx...
*December 29, 2012*

**algebra**

In google type: functions graphs online When you see list of results click on: rechneronline.de/function-graphs When page be open in blue recatacangle type: 3x+3 In grey rectacangle type: -x-3 Then click option Draw
*December 21, 2012*

**Pre Algebra Help ASAP**

a. 3 x – 3 = – 4 x Add 4x to both sides 3 x – 3 + 4 x = – 4 x 4 x 7 x - 3 = 0 Add 3 to bozh sides 7 x - 3 + 3 = 0 + 3 7 x = 3 Divide both sides by 7 x = 3 / 7 ONLY ONE SOLUTION b. 2 y + 4 – y = 16 y + 4 = 16 Subtracr 4 to both sides y + 4 - 4 = 16 - 4 ...
*December 21, 2012*

**Pre-Algebra**

5 h – 9 = – 16 + 6 h Add 9 to both sides 5 h – 9 + 9 = – 16 + 6h + 9 5 h = – 7 + 6h Subtract 5 h to both sides 5 h - 5 h = - 7 + 6 h - 5 h 0 = - 7 + h Add 7 to both sides 0 + 7 = - 7 + h + 7 7 = h h = 7 Proof : 5 h – 9 = – 16 + 6 h 5 * 7 - 9...
*December 20, 2012*

**math**

8 ( n - 3 ) / 3 = 32 Multiply both sides by 3 8 ( n - 3 ) = 96 Divide both sides by 8 n - 3 = 12 Add 3 to both sides n = 15
*December 17, 2012*

**calculus**

a. When x = sqrt ( 5 ) f ( x ) = 10 x ^ 2 / ( x ^ 4 + 25 ) = 10 * sqrt ( 5 ) ^ 2 / ( sqrt ( 5 ) ^ 4 + 25 ) = 10 * 5 / ( 25 + 25 ) = 50 / 50 = 1 yes b. When x = 3 f ( x ) = 10 x ^ 2 / ( x ^ 4 + 25 ) = 10 x ^ 2 / ( x ^ 4 + 25 ) = 10 * 3 ^ 2 ( 3 ^ 4 + 25 ) = 10 * 9 / ( 81 + 25...
*December 16, 2012*

**algebra**

Which points?
*December 16, 2012*

**math final review (help)**

Type your question in google. When you see list of result go on : algebra dot com
*December 16, 2012*

**math need help**

5 , 50 7 , 62 8 , 68 10 , 80 12 , 92 Different : 7 - 5 = 2 62 - 50 = 12 12 / 2 = 6 That mean : y increases for 6 when x increases for 1 That is slope. Slope intercept equation of straight line : y = m ( x + x1 ) + y1 In this case : m = ( y2 - y1 ) / ( x2 - x1 ) You can take ...
*December 16, 2012*

**Algebra 2**

( 2 - 5i ) - ( 3 + 4i ) = 2 - 5i - 3 - 4i = - 1 - 9i = - ( 1 + 9i )
*December 13, 2012*

**Math help**

d = diagonal L = Length W = Width d ^ 2 = L ^ 2 + W ^ 2 50 ^ 2 = 48 ^ 2 + W ^ 2 2500 = 2304 + W ^ 2 Subtract 2304 to both sides 2500 - 2304 = 2304 + W ^ 2 - 2304 196 = W ^ 2 W = sqrt ( 196 ) W = + OR - 14 Width can't be negative so W = 14 cm
*December 13, 2012*

**Solve for x math help**

x - 4 = sqrt ( 12 ) x - 4 = sqrt ( 4 * 3 ) x - 4 = 2 sqrt ( 3 ) x = 2 sqrt ( 3 ) + 4 x = 2 [ sqrt ( 3 ) + 2 ]
*December 13, 2012*

**math**

a = first number b = second number b = a + 2 a + 5 ( a + 2 ) = 58 a + 5 a + 10 = 58 6 a + 10 = 58 Subtrac 10 to both sides 6 a + 10 - 10 = 58 - 10 6 a = 48 Divide both sides by 6 6 a / 6 = 48 / 6 a = 8 b = a + 2 = 8 + 2 = 10 Your numbers are 8 and 10 8 + 5 * 10 = 8 + 50 = 58
*December 12, 2012*

**math/algebra**

L = W + 5 A = L * W ( W + 5 ) * W = 66 W ^ 2 + 5 W = 66 W ^ 2 + 5 W - 66 = 0 Solutions of equation are : W = - 11 and W = 6 Length can't be negative so : W = 6 cm Proof: L = W + 5 = 6 + 5 = 11 A = L * W = 11 * 6 = 66 cm ^ 2
*December 9, 2012*

**math**

4 a + ( 4a + 3 ) = 8 a + 3
*December 5, 2012*

**Math**

20 / 45 = 5 * 4 / ( 5 * 9 ) = 4 / 9 Answer D
*December 5, 2012*

**maths**

That is true for any value of a example: 3 ( x ^ 2 - 2 x ) = 0 has roots 0 and 2 7 ( x ^ 2 - 2 x ) = 0 has roots 0 and 2 39 ( x ^ 2 - 2 x ) = 0 has roots 0 and 2 etc.
*December 4, 2012*

**maths**

a is leading coefficient
*December 4, 2012*

**maths**

a x ^ 2 + b x + c = a ( x - x1 ) ( x - x2 ) In this case : a x ^ 2 + b x + c = a ( x - 0 ) ( x - 2 ) = a x ( x - 2 ) = a ( x ^ 2 - 2 x )
*December 4, 2012*

**trigonometry**

sec x = 1 / cos x sec x - cos x = 1 / cos x - cos x = 1 / cos x - cos ^ 2 x / cos x = ( 1 - cos ^ 2 x ) / cos x ________________________________________ Remark : 1 - cos ^ 2 x = sin ^ 2 x _______________________________________ 1 / cos x - cos ^ 2 x / cos x = ( 1 - cos ^ 2 x...
*December 4, 2012*

**math**

an = 2 * n + 1 For n = 1 a1 = 2 * 1 + 1 = 2 + 1 = 3 For n = 2 a2 = 2 * 2 + 1 = 4 + 1 = 5 etc.
*December 1, 2012*

**maths**

4 1 \ 6 = 4 + 1 / 6 = 24 / 6 + 1 / 6 = 25 / 6
*December 1, 2012*

**algebra**

6 x ^ 3 - 2 x = - 9 x ^ 2 Add 9 x ^ 2 to both sides 6 x ^ 3 - 2 x + 9 x ^ 2 = - 9 x ^ 2 + 9 x ^ 2 6 x ^ 3 + 9 x ^ 2 - 2 x = 0 x * ( 6 x ^ 2 + 9 x - 2 )= 0 You equation have 3 solutions: Obviously solution x = 0 Equation : 6 x ^ 2 + 9 x - 2 = 0 have two solutions : x1/2= [ - 9...
*November 26, 2012*

**math**

2 x ^ 2 + 6 x + 3 = 0 Compare your equation to the standard form : a x ^ 2 + b x + c = 0 and identify the values for a , b , c. a = 2 b = 6 c = 3 Now evaluate the discriminant : b ^ 2 - 4 a c = 6 ^ 2 - 4 * 2 * 3 = 36 - 24 = 12 Since b ^ 2 - 4 ac > 0 there are two unequal ...
*November 26, 2012*

**Math**

C = ( 5 / 9 ) ( F - 32 ) Multiply both sides by 9 9 C = 5 ( F - 32 ) Divide both sides by 5 ( 9 / 5 ) C = F - 32 Add 32 to both sides ( 9 / 5 ) C + 32 = F - 32 + 32 ( 9 / 5 ) C + 32 = F F = ( 9 / 5 ) C + 32
*November 22, 2012*

**matg**

V = A * h V = 45 * 8 = 360 m ^ 3
*November 22, 2012*

**precalculus**

If yourexpression mean : an = 3 a ( n − 1 ) + 9 a1 = 2 then a2 = 3 a1 + 9 = 3 * 2 + 9 = 6 + 9 = 15 a3 = 3 a2 + 9 = 3 * 15 + 9 = 45 + 9 = 54 a4 = 3 a3 + 9 = 3 * 54 + 9 = 162 + 9 = 171 a5 = 3 a4 + 9 = 3 * 171 + 9 = 513 + 9 = 522
*November 22, 2012*

**precalculus**

an = ( - 1 ) ^ n + 7 For odd numbers 1 , 3 , 5 ... ( - 1 ) ^ n = - 1 and ( - 1 ) ^ n + 7 = - 1 + 7 = 6 For even numbers 2 , 4 , 6 ... ( - 1 ) ^ n = 1 and ( - 1 ) ^ n + 7 = 1 + 7 = 8
*November 22, 2012*

**precalculus**

an = ( 1 / 2 ) ^ n a1 = 1 / 2 a2 = 1 / 2 ^ 2 = 1 / 4 a3 = 1 / 2 ^ 3 = 1 / 8 a4 = 1 / 2 ^ 4 = 1 / 16 a5 = 1 / 2 ^ 5 = 1 / 32 a6 = 1 / 2 ^ 6 = 1 / 64 1 / 2 + 1 / 4 + 1 / 8 + 1 / 16 + 1 / 32 + 1 / 64 = 63 / 64
*November 21, 2012*

**precalculus**

The sum of the members of a arithmetic progression : Sn = ( n / 2 ) * [ 2 a1 + ( n - 1 ) * d ] d = common difference of successive members of arithmetic progression In this case : S1 = ( 1 / 2 ) * [ 2 * 2 + ( 1 - 1 ) * 3 ] S1 = ( 1 / 2 ) * (4 + 0 * 3 ) S1 = ( 1 / 2 ) * 4 = 2 ...
*November 21, 2012*

**trig**

cos theta = sqrt ( 3 ) / 2 for theta = pi /6 and and theta = 11 pi / 6 Solutions : 3 x - pi / 2 = pi / 6 3 x = pi / 6 + pi / 2 3 x = pi / 6 + 3 pi / 6 3 x = 4 pi / 6 3 x = 2 pi / 3 Divide both sides by 3 x = 2 pi / 9 AND 3 x - pi / 2 = 11 pi / 6 3 x = 11 pi / 6 + pi / 2 3 x = ...
*November 20, 2012*

**Algebra 2**

A = Area W = Width L = Length L = 1.6 W A = L * W A = 1.6 W * W A = 1.6 W ^ 2 2,560 = 1.6 W ^ 2 Diwide both sides by 1.6 2,560 / 1.6 = W ^ 2 1600 = W ^ 2 W = sqrt ( 1600 ) = 40 in L = 1.6 * 40 = 64 in Answer: 40 in by 64 in
*November 18, 2012*

**algebra**

First byou must find real solution. x ^ 3 - 8 = 0 Add 8 to both sides x ^ 3 - 8 + 8 = 0 + 8 x ^ 3 = 8 x = third root of 8 = 2 In this case one rational zero is x = 2 Now you divide polynomial x ^ 3 - 8 with ( x - 2 ) ( x ^ 3 - 8 ) / ( x - 2 ) = x ^ 2 + 2 x + 4 OR ( x ^ 3 - 8...
*November 18, 2012*

**algebra**

Common factor of 4 x ^ 3 - 20 x ^ 2 + 24 x are 4x 4 x ^ 3 - 20 x ^ 2 + 24 x / 4 x = x ^ 2 - 5 x + 6 OR 4 x ^ 3 - 20 x ^ 2 + 24 x = 4 x * ( x ^ 2 - 5 x + 6 ) 4 x = 0 when x = 0 Solutions of equation : x ^ 2 - 5 x + 6 are x = 2 and x = 3 Solutions of equation : 4 x ^ 3 - 20 x ^ ...
*November 18, 2012*

**algebra**

a x ^ 4 + b x ^ 3 + c x ^ 2 + d x + e = a * ( x - x1 ) * ( x - x2 ) * ( x - x3 ) * ( x - x4 ) In tis case : a * ( x - 1 ) * ( x - 2 ) * ( x + 3 ) * ( x + 3 ) = a * ( x ^ 4 + 3 x ^ 3 - 7 x ^ 2 - 15 x + 18 )
*November 18, 2012*

**Math**

S = Numbers of students Percent of boys. 100 % - 55 % = 45 % = 45 / 100 45 % S = 18 45 S / 100 = 18 Multiply both sides by 100 45 S = 18 * 100 45 S = 1800 Divide both sides by 45 S = 1800 / 45 = 40
*November 18, 2012*

**Math**

80 * 75 % = 80 * 75 / 100 = 6000 / 100 = 60 100 * 95 % = 100 * 95 / 100 = 9500 / 100 = 95 70 * 70 % = 70 * 70 / 100 = 49 [ ( 60 + 95 + 49 ) / ( 80 + 100 + 70 ) ] * 100 % = ( 204 / 250 ) * 100 % = 0.816 * 100 % = 81.6 %
*November 18, 2012*

**math**

( 4 / 3 ) ^ 2 = 16 / 9 - ( 4 / 3 ) ^ 2 = - 16 / 9 ( 4 / 3 ) ^ 0 = 1 ( - 4 / 3 ) ^ 2 = 16 / 9 - ( - 4 / 3 ) ^ 2 = 16 / 9 ( 4 / 3 ) ^ 2 = 16 / 9 - ( 4 / 3 ) ^ 2 = - 16 / 9 abs ( - 16 / 9 ) = 16 / 9 -( 4 / 3 ) ^ 2 + ( 4 / 3 ) ^ 0 + 4 / 3 -( -4 / 3 ) ^ 2 +abs ( - (4 / 3 ) ^ 2...
*November 18, 2012*

**Math**

- 48 a ^ 6 b ^ 10
*November 15, 2012*

**number problem**

a = first number b = second number b = 3 a + 1 a + b = 9 a + 3 a + 1 = 9 4 a + 1 = 9 Subtract 1 to both sides 4 a + 1 - 1 = 9 - 1 4 a = 8 Divide both sides by 4 a = 8 / 4 a = 2 b = 3 a + 1 b = 3 * 2 + 1 b = 6 + 1 b = 7 Your number : 27
*November 14, 2012*

**Math**

d ( 2 x + 5 ) / dx = 0 2 = 0 Makes no sense. That is why critical number not exist.
*November 14, 2012*

**Math**

A number where first derivation = 0 is called a critical number. In this case : d ( 2 x + 5 ) / dx = = 2 = 0 Critical number of the fuction G(x)= 2 x + 5 not exist
*November 14, 2012*

**math 1**

( a1 + a2 + a3 + a4 + a5 + a6 + a7 + a8 + a9 + a10 ) / 10 = 12 Multiply both sides by 10 a1 + a2 + a3 + a4 + a5 + a6 + a7 + a8 + a9 + a10 = 120 ( a1 + a2 + a3 + a4 + a5 + a6 + a7 + a8 + a9 ) / 9 = 11 Multiply both sides by 9 a1 + a2 + a3 + a4 + a5 + a6 + a7 + a8 + a9 = 99 ( a1...
*November 14, 2012*

**calculus**

Go on : calc101 dot com When page be open click option : derivatives When page be open type your function and clik option : DO IT You will see solution step-by-step Remark : If expresion for f(x) mean : cos pi* ( x ^ 2 ) type : cos[pi]*x^2 If expresion for f(x) mean : cos ( pi...
*November 14, 2012*

**Math**

1. 9 x - 2 x = 7 x 2. - 3 y - 30 y = - 33 y 3. 2 a - 9 a = - 7 a
*November 10, 2012*

**algebra**

If your expression mean : 3 / a + 2 a / 3 a = 11 / 15 Then : 3 / a + 2 a / 3 a = 11 / 15 you can write like : 3 / a + 2 / 3 = 11 / 15 3 / a + 10 / 15 = 11 / 15 _____________________________ ( Becouse 2 / 3 = 10 / 15 ) _____________________________ Subtract 10 / 15 to both ...
*November 6, 2012*

**algebra**

If your expression mean : 3 / a + 2 / 3 a = 11 / 15 Then : 3 * 3 / ( 3 * a ) + 2 / 3 a = 11 / 15 9 / 3 a + 2 / 3 a = 11 / 15 11 / 3 a = 11 / 15 Multiply both sides by 3a 11 * 3 a / 3 a = 11 * 3 a / 15 11 = 33 a / 15 Multiply both sides by 15 11 * 15 = 33 a 165 = 33 a Divide ...
*November 6, 2012*

**Math**

24 / 12 = 2 2 24/12 = 2 + 24 / 12 = 2 + 2 = 4
*November 5, 2012*

**Math**

14 / 30 = 2 * 7 / ( 2 * 15 ) = 7 / 15
*November 2, 2012*

**Math**

Correction: In this case : m = 6 / 7 b = - 5
*October 31, 2012*

**Math**

y = m x + b This is called the slope-intercept form because "m" is the slope and "b" gives the y-intercept. In this case : b = 6 / 7 m = - 5 y = m x + b y = ( 6 / 7 ) x + ( - 5 ) y = ( 6 / 7 ) x - 5 Multiply both sides by 7 7 y = 6 x - 35 Subtract 6 x to ...
*October 31, 2012*

**Math for Steve**

14. 24 / 20 = 2 * 2 * 2 * 3 / ( 2 * 2 * 5 ) = 2 * 3 / 5 = 6 / 5
*October 30, 2012*

**calculus**

( x ^ 2 - 4 ) / ( x - 2 ) = ( x + 2 ) * ( x - 2 ) / ( x - 2 ) = x + 2 lim ( x ^ 2 - 4 ) / ( x - 2 ) as x->2 = lim ( x + 2 ) as x->2 = 2 + 2 = 4 ( x + 1 )/ ( x - 1 ) = 2 / ( x - 1 ) + 1 lim ( x + 1 )/ ( x - 1 ) as x->1 = lim [ 2 / ( x - 1 ) + 1 ] as x->1 = + OR - ...
*October 27, 2012*

**math**

In google type : quadratic equation calculator steps When you see list of results click on : algebra . com / algebra / homework / quadratic / When page be open type your equation and click option : Submit Query You will see solution
*October 26, 2012*

**algebra**

4 < 1 + n /7 Multiply both sides by 7 28 < 7 + n Subtract 7 to both sides 28 - 7 < 7 + n - 7 21 < n This is equivalent of : n > 21
*October 25, 2012*

**math**

16 x - y = 8 Add y to both sides 16 x - y + y = 8 + y 16 x = 8 + y Subtract 8 to both sides 16 x - 8 = 8 + y - 8 16 x - 8 = y y = 16 x - 8
*October 25, 2012*

**math**

324 = 3 * 108 324 * 4 = 3 * ( 108 * 4 )
*October 24, 2012*

**math**

1 1 / 4 = 1.25 6 2 / 8 = 6 1 / 4 = 6.25 1 * 6.25 / 1.25 = 1 * 5 = 5 signs
*October 24, 2012*

**prealgebra**

1 km = 1,000 m 1 min = 60 s 0.85 km / s = 0.85 * 1,000 * 60 = 850 * 60 = 51,000 m / min
*October 22, 2012*

**math**

1 bilion = 1,000 * 1,000,000 1 milon = 1,000 * 1,000 1 bilion = 1,000 * 1,000 * 1,000 = 1,000 ^ 3 1,000 = 10 ^ 3 1 bilion = ( 10 ^ 3 ) ^ 3 = 10 ^ 9 10 = 2 * 5 1 bilion = ( 2 * 5 ) ^ 9 = 2 ^ 9 * 5 ^ 9
*October 22, 2012*

**math**

L = Length B = Breadth P = Perimeter P = 2 L + 2 B = 2 ( L + B ) 26 = 2 ( L + B ) Divide both sides by 2 26 / 2 = 2 ( L + B ) / 2 13 = L + B Substract L to both sides 13 - L = L + B - L 13 - L = B B = 13 - L 1.) L = 1 cm B = 13 - 1 = 12 cm 2.) L = 2 cm B = 13 - 2 = 11 cm 3.) L...
*October 21, 2012*

**maths**

H = Height 3 m + 2 m = 5 m Proportion : H / 2 = 6.1 / 5 Multiply both sides by 2 H = 6.1 * 2 / 5 = 12.2 / 5 = 2.44 m
*October 21, 2012*

**Trigonometry**

cos ( 2 x ) = 2 cos ^ 2 ( x ) - 1 6 cos ^ 2 ( x ) - 3 = 3 [ 2 cos ^ 2 ( x ) - 1 ] = 3 sin ( 2 x )
*October 21, 2012*

**Math**

y - intercept for x = 0 y = 3 * 0 + 2 = 0 + 2 = 2 x - intercept 3 x + 2 = 0 3 x = - 2 x = - 2 / 3 Plot coordinate system. Them mark points : x = 0 ; y = 2 and x = - 2 / 3 ; y = 0 Then drawe straight line.
*October 13, 2012*

**pre-cal**

d = sqrt [ ( x2 - x1 ) ^ 2 + ( y2 - y1 ) ^ 2 ] In this case : x1 = - 1 y1 = 1 x2 = 1 y2 = 2 d = sqrt [ ( 1 - ( - 1 ) ) ^ 2 + ( 2 - 1 ) ^ 2 ] d = sqrt [ ( 1 + 1 ) ) ^ 2 + 1 ^ 2 ] d = sqrt [ 2 ^ 2 + 1 ] d = sqrt ( 4 + 1 ) d = sqrt ( 5 )
*October 12, 2012*

**algebra**

What is your question?
*October 7, 2012*

**math**

7.185 * 10 ^ 2
*October 6, 2012*

**math**

84.5 < 90 Decrese [ 1 - ( 84.5 / 90 ) ] * 100 % = ( 1 - 0.938888 ... ) * 100 % = 0.061111 ... * 100 % = 6.1111 %
*October 5, 2012*

**maths magic**

9 + 8 + 7 + 6 + 5 + 4 + 3 + 2 + 1 = 45 Write 45 like : 987654321 1 + 2 + 3 + 4 + 5 + 6 + 7 + 8 + 9 = 45 Write 45 like : 123456789 987654321 - 123456789 = 864197532 8 + 6 + 4 + 1 + 9 + 7 + 5 + 3 + 2 = 45 987654321 [ 45 ] - 123456789 [ 45 ] = 864197532 [ 45 ]
*October 5, 2012*

**college algebra**

x ^ 6 - 64 = 0 Add 64 to both sides x ^ 6 - 64 + 64 = 0 + 64 x ^ 6 = 64 x = sixth root of 64 x = + OR - 2 Solutions : x = - 2 and x = 2
*October 5, 2012*

**Precalc**

x ^ 2 - x y + 2 x - 1 = 0 Add xy to both sides x ^ 2 - x y + 2 x - 1 + x y = 0 + x y x ^ 2 + 2 x - 1 = x y Roots : When y = 0 then : x ^ 2 + 2 x - 1 = x * 0 x ^ 2 + 2 x - 1 = 0 Add 2 to both sides x ^ 2 + 2 x - 1 + 2 = 0 + 2 x ^ 2 + 2 x + 1 = 2 ...
*October 4, 2012*

**math**

1 basket : 12 a + b = 3105 Subtract 12 a to both sides 12 a + b - 12 a = 3105 - 12 a b = 3105 - 12 a
*October 4, 2012*

**math**

a = mass of one aple b = mass of basket 1 basket : 12 a + b = 3105 Subtract 12 a to both sides 12 a + b - 12 b = 3105 - 12 a b = 3105 - 12 a 2 basket : 7 a + b = 1980 7 a + 3105 - 12 a = 1980 - 5 a + 3105 = 1980 Subtract 3105 to both sides - 5 a + 3105 - 3105 = 1980 - 3105 - 5...
*October 4, 2012*

**precalc**

( a + b ) ^ 3 = a ^ 3 + 3 a ^ 2 b + 3 a b ^ 2 + b ^ 3 ( x + 2 ) ^ 3 = x ^ 3 + 3 x ^ 2 * 2 + 3 x * 2 ^ 2 + 2 ^ 3 = x ^ 3 + 3 x ^ 2 * 2 + 3 x * 4 + 8 = x ^ 3 + 6 x ^ 2 + 12 x + 8 - 3 x ^ 2 * ( x ^ 3 + 6 x ^ 2 + 12 x ) = - 3 x ^ 5 - 18 x ^ 4 - 36 x ^ 3 the degree of a polynomial...
*October 4, 2012*

**ALG2!**

- 3 k - 8 < = 5 k Subtract 5 k to both sides - 3 k - 8 - 5 k < = 5 k - 5 k - 8 k - 8 < = 0 Add 8 to both sides - 8 k - 8 + 8 < = 0 + 8 - 8 k < = 8 Divide both sides by - 8 ________________________________________ Remark : If you multiply or divide both sides of ...
*October 4, 2012*

**math**

J = Jim age C = Carol age J = 45 J = 10 + 5 C 45 = 10 + 5 C Subtract 10 to both sides 45 - 10 = 10 + 5 C - 10 35 = 5 C Divide both sides by 5 35 / 5 = C 7 = C C = 7 Carol is 7 yo Proof : 5 * 7 + 10 = 35 + 10 = 45
*October 3, 2012*

**PRECALC**

2 sin 4 x = 1 Divide both sides by 2 sin 4 x = 1 / 2 Take the inverse sine of both sides : 4 x = sin ^ - 1 ( 1 / 2 ) ________________________________________ Remark : sin ^ - 1 ( 1 / 2 ) = pi / 6 + 2 pi n OR 5 pi / 6 + 2 pi n Where n is an integer ...
*October 3, 2012*

**Algebra**

-107
*October 1, 2012*

**math**

6 d - 3 d + 2 d = 35 5 d = 35 Divide both sides by 5 d = 7
*September 26, 2012*

**Calculus**

ln ( x ^ 4 ) = 4 * ln ( x ) ln ( x ^ 2 ) = 2 * ln ( x ) ln ( x ^ 4 ) - ln ( x ^ 2 ) = 2 4 * ln ( x ) - 2 * ln ( x ) = 2 2 * ln ( x ) = 2 Divide both sides by 2 ln ( x ) = 1 Cancel logarithm by taking exp of both sidess x = e = 2.71828...
*September 24, 2012*

**Geometry**

Two Angles are Complementary if they add up to 90 ° In this case : 16 z - 9 ° + 4 z + 3 ° = 90 ° 20 z - 6 ° = 90 ° Add 6 ° to both sides 20 z - 6 ° + 6 ° = 90 ° + 6 ° 20 z = 96 ° Divide both sides by 20 z = 96 ° / 20 = 4.8 &...
*September 17, 2012*

**Algebra2**

1. 5 x - y = 10 5 x - 10 = y y = 5 x - 10 2. x ^ 2 + y ^ 2 = 4 y ^ 2 = 4 - x ^ 2 y = + OR - sqrt ( 4 - x ^ 2 )
*September 17, 2012*

**Algebra 2**

Go on : wolframalpha dot com When page be open in rectangle type : solve x-3x^1/2+2=0 an click option : = When you seeresults click option : Show steps
*September 17, 2012*

**Algebra 2**

Go on : wolframalpha dot com When page be open in rectangle type : solve 6X^(2/3)-5X^(1/3)-6=0 an click option : = When you seeresults click option : Show steps
*September 17, 2012*

**Arithmetic Progression**

Arithmetic progression : an = a1 + ( n - 1 ) * d In this case : a6 = a1 + ( 6 - 1 ) * d a6 = a1 + 5 d a4 = a1 + ( 4 - 1 ) *d a4 = a1 + 3 d a6 = ( 1 / 2 ) a4 a6 = ( 1 / 2 ) ( a1 + 3 d ) a6 = a1 / 2 + 3 d / 2 a6 = a6 a1 + 5 d = a1 / 2 + 3 d / 2 Substract 5 d to both sides a1 + 5...
*September 17, 2012*

**algebra**

2 ( 5 + k ) = 10 + 2 k
*September 17, 2012*

**Algebra**

Sorry last row : = ( 3 a ^ 2 b - 4 a b ^ 2 + 2 b ^ 4 ) / 2 a
*September 17, 2012*

**Algebra**

( 9 a ^ 3 b ^ 4 - 12 a ^ 2 b ^ 5 + 6 a b ^ 7) / ( 6 a ^ 2 b ^3 ) = 3 * a * b ^ 3 * ( 3 a ^ 2 * b - 4 a * b ^ 2 + 2 b ^ 4 ) / [ 3 * a * b ^ 3 * ( 2 a ) ] = ( 3 a ^ 2 b - 4 a b ^ 2 + 2 b ^ 4 ) / 20
*September 17, 2012*